PENGARUH PENDIDIKAN KEWIRAUSAHAAN BERBBASIS PROYEK TERHADAP MINAT BERWIRAUSAHA SISWA KELAS XII PADA MATERI PERENCANAAN USAHA PENGOLAHAN MAKANAN FUNGSIONAL - Octaviany, Fany; Yayat Ruhiyat; Cucu Atikah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The unemployment rate for high school and vocational school students continues to be the highest until February 2024, there were 7.2 million unemployed people recorded in Indonesia according to data from (Indonesian Central Statistics Agency, 2024). And increasing the number of entrepreneurs is the best alternative to reduce unemployment in Indonesia. Therefore, the government, through the Ministry of Education and Culture, Research and Technology, included entrepreneurship education in the 2013 curriculum. Entrepreneurship education with a project based learning model was chosen because it is expected to increase students' interest in entrepreneurship. Because in PjBL students not only receive learning, but also gain direct experience of becoming entrepreneurs. This research uses a quantitative descriptive method. Data analysis in this research uses SPSS 25. The results of this research are that the correlation between the two variables has a significant positive effect, meaning that the higher the level of entrepreneurship education, the higher the interest in entrepreneurship.